Ubiquitination regulation of mitochondrial homeostasis: a new sight for the treatment of gastrointestinal tumors - Huang, Bingqian; Yang, Yulin; Liu, Jinming; Zhang, Biao; Lin, Nengming (Frontiers in Immunology, 2025)
Mitochondrial homeostasis (MH) refers to the dynamic balance of mitochondrial number, function, and quality within cells. Maintaining MH is significant in the occurrence, development, and clinical treatment of Gastrointestinal (GI) tumors. Ubiquitination, as an important post-translational modification mechanism of proteins, plays a central role in the regulation of MH. Over the past decade, research on the regulation of MH by ubiquitination has focused on mitochondrial biogenesis, mitochondrial dynamics, Mitophagy, and mitochondrial metabolism during these processes. This review summarizes the mechanism and potential therapeutic targets of ubiquitin (Ub)-regulated MH intervention in GI tumors.